Sumber-Sumber Tafsir Al-Qur’an dari Masa ke Masa: Pemetaan Riwayah, Dirayah, Isyarah, dan Isra’iliyyat - Hasanuddin Sinaga (LaKaspia, 2025)
The sources of Qur’anic interpretation refer to the references used to understand the meanings of the verses, both as explanatory tools and as comparative frames in the process of exegesis. Differences in the use of these sources have contributed to the diversity of interpretive approaches and exegetical products throughout Islamic history, without implying that any single interpretation is absolute. This article employs a descriptive and analytical library-based approach to map four major sources of Qur’anic interpretation discussed in the literature, namely al-riwāyah (transmitted reports), ad-dirāyah (al-ra’y or rational reasoning), al-isyārah (intuitive or allusive interpretation), and isrā’īliyyāt (narratives originating from the Ahl al-Kitāb tradition). The analysis shows that al-riwāyah maintains the connection between interpretation and early authoritative traditions, ad-dirāyah expands exegetical engagement through scholarly reasoning and methodological tools, al-isyārah enriches the ethical and spiritual dimensions of interpretation as long as it does not negate the outward meaning of the text, and isrā’īliyyāt is generally treated in a limited manner as supplementary narrative material subject to strict scrutiny. This mapping indicates that the dynamics of Qur’anic interpretation are shaped by the complementary interaction of these sources in response to changing historical and intellectual contexts.